Using a relational database to support nursing research. - Boyington AR; Tomlinson BU; Dougherty MC (Computers in Nursing)
Designing, implementing, and maintaining a relational database for a complex, longitudinal clinical research project can be the key to the success of a research project. Related issues of data entry, accuracy, confidentiality, security, data analysis, and evaluation of research activities are among the considerations that must be addressed. Our experience with designing a system that was effective and user-friendly to manage the data collected during a 6-year, National Institutes of Health-funded, nursing research project is highlighted. Nurses and other healthcare providers may find our experience with a relational database helpful and applicable to similar clinical research projects.